2021
DOI: 10.1177/23727322211033005
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Young Children’s Development of Executive Function Through Early Mathematics

Abstract: Early childhood teachers face competing instructional priorities to support specific academic skills and general skills that underlie learning, such as executive function (EF) skills that allow children to control their own thinking and behavior. As the evidence shows, EF skills predict later mathematics achievement, and early mathematics predicts later EF. These relations between mathematics and EF suggest high-quality mathematics teaching has a dual benefit: Teachers can promote children’s math and EF compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…It is interesting to note that development of EF is bidirectional. For example, it was reported that EF improved significantly when training was carried out with instructional activities of high-quality mathematics (and literacy), even without targeting EF specifically (Farran et al, 2011;Mulcahy et al, 2021). These findings coincide with the theory supported by findings showing that optimal learning of mathematics and EF is influenced by the bidirectional relations between these two domains (Blair, 2002;Sarama and Clements, 2009;Williford et al, 2013;Clements et al, 2016).…”
Section: The Effects Of Training For Self-regulation On Math Skillsmentioning
confidence: 63%
See 1 more Smart Citation
“…It is interesting to note that development of EF is bidirectional. For example, it was reported that EF improved significantly when training was carried out with instructional activities of high-quality mathematics (and literacy), even without targeting EF specifically (Farran et al, 2011;Mulcahy et al, 2021). These findings coincide with the theory supported by findings showing that optimal learning of mathematics and EF is influenced by the bidirectional relations between these two domains (Blair, 2002;Sarama and Clements, 2009;Williford et al, 2013;Clements et al, 2016).…”
Section: The Effects Of Training For Self-regulation On Math Skillsmentioning
confidence: 63%
“…Several researchers conceptualized planning behavior along with inhibition of impulsivity and working memory (WM) as central components of EF system (e.g., Lehto et al, 2003;Naglieri and Das, 2005;Cutting et al, 2009;Clark et al, 2010) and highly predictive of math performance (McLean and Hitch, 1999;Naglieri and Johnson, 2000;Bull and Scerif, 2001;Passolunghi and Siegel, 2001;Espy et al, 2004;van der Sluis et al, 2007;D'Amico and Guarnela, 2005;Blair and Razza, 2007;De Corte, 2007;Lan et al, 2011;Allan et al, 2014;Bull and Lee, 2014;Cai et al, 2016;Clements et al, 2016;Giofrè et al, 2018;Mulcahy et al, 2021). According to Lehto et al (2003) the three EF components are: working memory, inhibition, and shifting.…”
Section: Self-regulation Planning Behavior and Math Performancementioning
confidence: 99%
“…Therefore, the EF guideline provides an option to develop early childhood schoolteachers in the processes of executive function-related issues. Apart from using Teacher-Child Interactions (Choi et al, 2016), including EFs in the teacher training (Corcoran & O'Flaherty, 2017;Manowaluilou, 2021), and teaching early mathematics (Mulcahy et al, 2021), the EF guideline can also be used in EF education for teachers.…”
Section: Discussionmentioning
confidence: 99%
“…It can be claimed that EF education plays a crucial role in early childhood education and the development of the skills rather starts with developing teachers' learning management abilities than applying instructional methods to early childhood classes. Consequently, studies have been conducted to develop early childhood teachers' abilities in managing EF education (e.g., Choi et al, 2016;Corcoran & O'Flaherty, 2017;Gilmore & Cragg, 2014;Manowaluilou, 2021;Mulcahy et al, 2021). What could be summarized from the result of the related studies is that the knowledge of executive function education is expected to be acquired by early childhood teachers.…”
Section: Related Studiesmentioning
confidence: 99%
“…Indeed, although interventions specifically aimed at training WM often showed no or only limited transfer effects to WM in daily life or academic contexts (Melby‐Lervåg et al, 2016; Redick et al, 2015), some studies did show the opposite: Higher‐order skills such as WM developed in the context of subject‐matter instruction and practice (e.g. using verbalizations), which in turn supported learning the subject matter (Clements et al, 2001; Mulcahy et al, 2021). As such, sex differences in WM ability may also evolve as a result of prolonged use and experience with certain strategies.…”
Section: Introductionmentioning
confidence: 99%